AN UNHEALTHY PSYCHOLOGICAL ENVIRONMENT IN THE FAMILY IS A FACTOR THAT CAUSES VIOLENCE. (Universal International Scientific Journal, 2026)
This article analyzes the impact of an unhealthy psychological environment in the family on the occurrence of violence. It scientifically examines how family conflicts, aggression, misunderstanding, and psychological pressure affect human psychology and behavior. It also provides psychological recommendations for the causes of family violence, its negative impact on society, and its prevention.
Keywords: family, psychological environment, violence, conflict, aggression, family relationships, psychological health.